Mechanical properties of spinal cord grey matter and white matter in confined compression. (December 2020) - Yu, Justin; Manouchehri, Neda; Yamamoto, Shun; Kwon, Brian K.; Oxland, Thomas R.
Abstract: To better understand the link between spinal cord impact and the resulting tissue damage, computational models are often used. These models typically simulate the spinal cord as a homogeneous and isotropic material. Recent research suggests that grey and white matter tissue differences and directional differences, i.e. anisotropy, are important to predict spinal cord damage. The objective of this research was to characterize the mechanical properties of spinal cord grey and white matter tissue in confined compression. Spinal cords (n = 12) were harvested immediately following euthanasia from Yorkshire and Yucatan pigs. The spinal cords were flash frozen (60 s at -80 °C) and prepared into four types of test samples: grey matter axial, grey matter transverse, white matter axial, and white matter transverse. Each sample type was thawed, and subsequently tested in confined compression within 6 h of euthanasia. Samples were compressed to 10% strain at a quasi-static strain rate (0.001/sec) and allowed to relax for 120 s. A quasi-linear viscoelastic model combining a first-order exponential with a 1-term Prony series characterized the loading and relaxation responses respectively. The effect of tissue type (grey matter vs. white matter), direction (axial vs. transverse), and their interaction were evaluated with a two-way ANOVA (p < 0.05) with peak stress, aggregate modulus, and relaxation time as dependent variables. This study found grey matter to be 1.6–2 times stiffer than white matter and both grey and white matter were isotropic in compression. These findings should be emphasized when studying SCI biomechanics using computational models. Graphical abstract: Image 1 Highlights: Biopsy punch design enabled sample collection and testing without sample removal. Mechanical behaviour of spinal cord tissue is strain-stiffening and viscoelastic. Grey matter tissue is stiffer than white matter tissue in compression. Grey matter tissue and white matter tissue are isotropic in compression. Modeling distinct tissue properties is more important than directional properties.